A note on the gender reservation wage gap in developing countries. (29th June 2020) - Khan, Bilal Muhammad; Majid, Muhammad Farhan
Abstract: This is the first paper to document the existence of a gender reservation wage gap in developing countries. We find a 22.6% gender reservation wage gap, a gap that is much larger than current estimates for developed countries. Assets play the largest role in closing this gap, whereas adult height widens the gap among the poor.